Individualized antibiotic dosage regimens for patients with augmented renal clearance - Shi, A-Xi; Qu, Qiang; Zhuang, Hai-Hui; Teng, Xin-Qi; Xu, Wei-Xin; Liu, Yi-Ping; Xiao, Yi-Wen; Qu, Jian (Frontiers in Pharmacology, 2023)
Objectives: Augmented renal clearance (ARC) is a state of enhanced renal function commonly observed in 30-65% of critically ill patients despite normal serum creatinine levels. Using unadjusted standard dosing regimens of renally eliminated drugs in ARC patients often leads to subtherapeutic concentrations, poor clinical outcomes, and the emergence of multidrug-resistant bacteria. We summarized pharmaceutical, pharmacokinetic, and pharmacodynamic research on the definition, underlying mechanisms, and risk factors of ARC to guide individualized dosing of antibiotics and various strategies for optimizing outcomes. Methods: We searched for articles between 2010 and 2022 in the MEDLINE database about ARC patients and antibiotics and further provided individualized antibiotic dosage regimens for patients with ARC. Results: 25 antibiotic dosage regimens for patients with ARC and various strategies for optimization of outcomes, such as extended infusion time, continuous infusion, increased dosage, and combination regimens, were summarized according to previous research. Conclusion: ARC patients, especially critically ill patients, need to make individualized adjustments to antibiotics, including dose, frequency, and method of administration. Further comprehensive research is required to determine ARC staging, expand the range of recommended antibiotics, and establish individualized dosing guidelines for ARC patients.